2001
DOI: 10.1093/jnen/60.11.1087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oncostatin M on Human Cerebral Endothelial Cells and Expression in Inflammatory Brain Lesions

Abstract: Oncostatin M (OSM) is a member of the interleukin (IL)-6 cytokine family and modulates inflammatory responses. Here we investigated the role of OSM as an immunoregulatory factor for human cerebral endothelial cells (HCEC). Using RT-PCR we detected transcripts of the receptor components involved in OSM signaling, gp130, OSM receptor (OSMR)-beta, and leukemia inhibitory factor receptor (LIFR), in HCEC. A parallel FACS analysis revealed surface expression of gp130 and OSMR-beta, but not of LIFR on these cells. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 57 publications
4
86
0
Order By: Relevance
“…We have previously reported that OSM is produced by microglia in culture (Kordula et al 1998). Recently, OSM has been detected in microglia, reactive astrocytes, and leukocytes infiltrating the brains of multiple sclerosis patients; whereas OSM was not expressed in normal brains or brains of patients with non-inflammatory neurological diseases (Ruprecht et al 2001). There are also numerous reports indicating that IL-1 is found in the CNS and it is involved in many physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that OSM is produced by microglia in culture (Kordula et al 1998). Recently, OSM has been detected in microglia, reactive astrocytes, and leukocytes infiltrating the brains of multiple sclerosis patients; whereas OSM was not expressed in normal brains or brains of patients with non-inflammatory neurological diseases (Ruprecht et al 2001). There are also numerous reports indicating that IL-1 is found in the CNS and it is involved in many physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is suggested by the observation of significantly reduced T-cell infiltration and diffuse microglia activation within the noninflamed spinal cord parenchyma and a significant reduction of Ig leakage in spinal cord tissue of 74 Although expression of CNTFR␣ mRNA was not detected, 74 requirement for the nonsignaling chain can be bypassed by the formation of complexes between CNTF and soluble CNTFR␣. 14 The CNTF doses used in our EAE experiments are in same range as other studies in which CNTF or LIF were administered systemically.…”
Section: Discussionmentioning
confidence: 99%
“…106 OSM may also promote BBB dysfunction by stimulating brain cells to produce cytokines and prostaglandins, 107,108 and to increase the expression of cell adhesion molecules on endothelial cells. 109 While monocytes are the dominant source of OCM produced by blood cells, activated microglia and astrocytes are additional sources of OCM in the brain. Monocytes are also a rich source of VEGF.…”
Section: Monocytesmentioning
confidence: 99%